Síntese de pirazolo[1,5-a]pirimidinas e fluorfenilpirazóis trifluormetilados em ultrassom e síntese e aplicação de [2]rotaxanos - Marzari, Mara Regina Bonini (2014)
This work presents the synthesis of three series of trifluoromethylated heterocycles by using ultrasound irradiation, nomely pyrazolo[1,5-a]pyrimidines, 2,4- difluorophenylpyrazoles and pentafluorophenylpyrazoles. The reactions were performed between trifluoromethylated enones ([CF3C(O)CH=C(R)(OMe], where R = Me, Bu, i-Bu, Ph, 4-MeC6H4, 4-FC6H4, 4-ClC6H4, 4-BrC6H4, 4-IC6H4, thien-2-yl, naphthyl and biphenyl) with three different nucleophiles, nomely (3)(5)-amine-(5)(3)- methylpyrazole, 2,4-difluorophenylhydrazine hydrochloride and pentafluorophenylhydrazine. The trifluoromethylated pyrazolo[1,5-a]pyrimidines were obtained within 5 minutes, giving yields of 61-98 %. The series of 2,4- difluorophenylpyrazoles was obtained in good yields (54-85 %) within 15 minutes by acidifying the reaction medium with PTSA. In the case of the pentafluorophenylpyrazoles, two steps were needed: Firtly the respective 4,5- dihydropentafluorophenylpyrazoles were synthesised and then subsequently submitted to dehydration reactions using PTSA for 15 minutes, giving yields of 54-81 %. The synthesized compounds were identified by 1H and 13C, and by 19F NMR spectroscopy in the some case, mass spectrometry and X-ray diffraction. In some cases homo/heteronuclear spatial interactions involving fluorine atoms have been useful for confirming the identity of the obtained isomer. Another part of this tesis was the synthesis of four mechanically interlocked molecules. Two [2]rotaxanes carrying an ester group in the macrocycle unity were synthesized by using two threads (fumaramide and succinamide derivatives). Once synthesized these [2]rotaxanes were submmited to hydrolysis reactions to give [2]rotaxanes with acid carboxilic group. These macromolecules were synthesized aiming at the formation of MOFs (metal organic frameworks). The synthesis of this compound was carried out by using copper (II) and [2]rotaxane derivative fumaramide. This product was identified by X-ray diffractometry.